Upaya Meningkatkan Hasil Belajar Membaca Melalui Metode SAS Pada Siswa Kelas I SDN 1 Demak Ijo Tahun Pelajaran 2023/2024 - Sri Utami; Bayu Purbha Sakti; Sri Suwartini (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to improve the reading learning outcomes of grade 1 students at SD Negeri 1 Demak ijo using the SAS method in Indonesian language subjects. Classroom Action Research (PTK) was carried out in two cycles where the cycle was held in one meeting. The subjects of this research were 19 grade 1 students at SD Negeri 1 Demak Ijo. Data collection techniques through tests, observation and documentation. The results of this research show that: (1) students became more fluent in reading, (2) there was an increase in reading learning outcomes in Indonesian language subjects for grade 1 students at SD Negeri 1 Demak Ijo. This increase is proven by the results of the pre-cycle test, the average class score was 63.2, then it increased in the first cycle to 75.7 and increased in the second cycle to 90. The percentage of completeness of learning outcomes during the pre-cycle was 68%, in the first cycle it was 68,42% and in cycle II, 84.21% achieved KKTP ≥ 75. From the research results above, it can be concluded that applying the SAS method can improve reading learning outcomes in Indonesian language subjects for grade 1 students at SD Negeri 1 Demak Ijo.